Thermodynamic modeling of the Sc-Zn system coupled with first-principles calculation - Tang C.; Zhou P.; Zhao D.D.; Yuan X.M.; Tang Y.; Wang P.S.; Hu B.; Du Y.; Xu H.H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The Sc-Zn system has been critically reviewed and assessed by means of CALPHAD (CALculation of PHAse Diagram) approach. By means of first-principles calculation, the enthalpies of formation at 0 K for the ScZn, ScZn2, Sc17Zn58, Sc3Zn17 and ScZn12 have been computed with the desire to assist thermodynamic modeling. A set of self-consistent thermodynamic parameters for the Sc-Zn system is then obtained. The calculated phase diagram and thermodynamic properties agree well with the experimental data and first-principles calculations, respectively.